2015
DOI: 10.19056/ijmdsjssmes/2015/v4i1/79944
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study to Evaluate Efficacy & Cost Effectiveness of Olmesartan Versus Telmisartan, in Patients of Stage I Hypertension

Abstract: Background: Hypertension is one of the most common diseases in the world. It is an important and independent risk factor for atherosclerosis, heart failure, renal disease, and peripheral arterial disease. It is directly responsible for 57% of all stroke deaths and 42% of coronary heart disease deaths in India Objectives: To evaluate and compare efficacy and cost effectiveness in hypertensive patients receiving Olmesartan and Telmisartan in Stage I hypertension Material and methods: The present study was an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Few other researchers [14,15] also supported our findings. Another explanation for greater BP lowering effect of olmesartan as compared to Telmisartan was explained in the study of Le et al; [16], which in addition reported that although both ARBs were competitive antagonist at but olmesartan had higher affinity, greater degree of unsorrmountability and slower dissociation from AT1 receptor than telmisartan.…”
Section: Baseline Investigations Done In All Patients -supporting
confidence: 92%
“…Few other researchers [14,15] also supported our findings. Another explanation for greater BP lowering effect of olmesartan as compared to Telmisartan was explained in the study of Le et al; [16], which in addition reported that although both ARBs were competitive antagonist at but olmesartan had higher affinity, greater degree of unsorrmountability and slower dissociation from AT1 receptor than telmisartan.…”
Section: Baseline Investigations Done In All Patients -supporting
confidence: 92%